European Gender Mainstreaming: Achievements and Challenges of Transformative Policy - Reingardienė, Jolanta (Sociologija. Mintis ir veiksmas, 2004)
Gender mainstreaming aims to enable the state to deliver gender-sensitive policy instruments and transform gender relations. It is a widely adapted approach that was developed in transnational networks of women activists, but goes beyond women’s policy machinery. Mainstreaming suggests that equal opportunities for women and men should no longer be achieved solely through traditional equal opportunities policies. The article analyses the historical development of gender mainstreaming approach, the promises and pitfalls of the transformative policy. The second part of the study analyses main ideological, institutional, political and legal obstacles to the implementation of gender mainstreaming in different national contexts, including Lithuania.